Influence of Pier Geometry on Flow Characteristics using CFD - Azheen Karim Fatah; Abdulla Abdulwahid Abo; Pshtiwan Othman Zaid; Arkan Hamza (Zanco Journal of Pure and Applied Sciences, 2025)
An important part of hydraulic engineering that is vital for the security and durability of bridge structures understands the velocity of water flow around bridge piers, and this is what this research aims to do. The flow characteristics around three different pier shapes—triangular, rectangular, and circular—were the primary focus of the investigation. The study tested the computational model against experimental data from a reputable source to make sure it was accurate. A discrepancy of less than 10% was found between the model's predictions and the actual experimental data, indicating a good degree of agreement. The results showed that the maximum flow rates just before the center piers varied with pier shape. The highest velocity recorded by the rectangular pier was 0.592 m/s, while the round and triangular piers reached 0.553 and 0.550 m/s, respectively. As one moved farther downstream, the velocity of all designs dropped significantly. At 0.261 m/s, the rectangular pier was the fastest, followed by the triangle at 0.256 m/s, and finally the round at 0.249 m/s. According to the findings, the smoother form of the circular pier is more successful at decreasing flow disturbance than that of the rectangular pier, which has sharper edges and a larger frontal surface and so disrupts the flow more. Findings from this research are crucial for hydraulic engineers because they show how to choose the right pier designs to increase the stability and longevity of bridges without altering the natural flow conditions.